Development and Characterisation of Fig (Ficus carica) Leaves Tea with Special Reference to Hypoglycemic Effect: Ficus Leaves Tea for Hypoglycemia - Gillani, Maham; Iftikhar, Hira; Lodhi, Asma; Pasha, Imran (Biological Sciences - PJSIR, 2018)